2007
DOI: 10.3390/medicina43070069
|View full text |Cite
|
Sign up to set email alerts
|

The importance of T-lymphocyte subsets on overall survival of colorectal and gastric cancer patients

Abstract: Summary. The aim of this study was to evaluate the influence of cellular immunity parametersMedicina (Kaunas) 2007; 43(7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
1
26
0
1
Order By: Relevance
“…Diederichsen et al [74] showed that a low CD4/CD8 ratio by flow cytometry was an independent prognostic factor for prolonged survival. In addition, Milasiene et al [75] evaluated inter-epithelial CD3, CD4, CD8, CD20 and CD16 and found that increased levels of all these markers, particularly of the natural killer cell marker CD16 led to significantly improved overall outcome [11,75] . Moreover, regulatory T-cells expressing FOXP3+ has been shown to correlate with improved outcome independently of TNM stage [16,76] .…”
Section: T-lymphocytesmentioning
confidence: 99%
“…Diederichsen et al [74] showed that a low CD4/CD8 ratio by flow cytometry was an independent prognostic factor for prolonged survival. In addition, Milasiene et al [75] evaluated inter-epithelial CD3, CD4, CD8, CD20 and CD16 and found that increased levels of all these markers, particularly of the natural killer cell marker CD16 led to significantly improved overall outcome [11,75] . Moreover, regulatory T-cells expressing FOXP3+ has been shown to correlate with improved outcome independently of TNM stage [16,76] .…”
Section: T-lymphocytesmentioning
confidence: 99%
“…An increased lymphocyte count has also been shown to be a prognostic factor for OS in patients with gastric and colorectal cancer (25,26). In addition, lymphocyte subsets have been shown to be predictive markers for immunotherapy in patients with cancer (14,27).…”
Section: Discussionmentioning
confidence: 99%
“…While the flow cytometry studirs did indicate significant changes in lymphocytes (and sunpopulations) levels among the cancer patients, unfortunately, the studies failed to yield overall lymphocyte (or subtipe) population patterns that paralleled the concurrent changes in ABM fluorescence example of this "lack of comparativeness"). The studie of Milasiene (Milasiene et al, 2007) also suggest that immunosuppression covers many aspects of the complex immune system, and therefore, we have many unexpected findings. The studies here also revealed significant changes in ABM fluorescence associated with the plasma (re: albumin) of the cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with gastrointestinal cancer exhibit a poorly functioning immune system that is characterized, in part, by decreases in T-lymphocyte proliferation (Greenstein, et al, 1991;Milasiene et al, 2007) and reduced CD4 + :CD8 + ratios (Arista et al, 1994;Franciosi et al, 2002). In different pathologies (including these and other types of cancers), membrane damage in immune cells (and other cell types) often evolves as a consequence of alterations that are induced in cell-associated lipids and proteins in the affected patients Dobretsov, 1994, 1998;Rolinsky et al, 2007).…”
Section: Introductionmentioning
confidence: 99%